PIDANA MATI BAGI PELAKU TINDAK PIDANA KORUPSI MENURUT SISTEM HUKUM DI INDONESIA - Muhammad Afdhal Askar (Institut Agama Islam Negeri Batusangkar, 2019)
The development of Corruption Crimes has a widespread adverse impact on the lives of Indonesian people life. To stop this, it is needed to be taken a variety of extraordinary efforts including by implementing capital punishment for perpetrators, especially related to criminal acts of corruption that concern to many people that occur when the country is in danger. Even so, not all people agree with the application of capital punishment because it is considered to be conflict with Human Rights, the Constitution of the Republic Indonesia and Pancasila. To analyze these legal issues, various efforts can be taken such as seeing the meaning of the nature of human rights in the perspective of national and international law, interpreting legal norms using appropriate interpretation methods and seeing the existence of capital punishment in the perspective of religious law and customary law. Writing in this study uses a normative juridical approach with the type of data in the form of secondary data which comes from primary legal material and secondary legal material. The writing is done descriptively.